Exploring the maternal inheritance transmitted by the oocyte to its progeny - Verlhac, Marie-Hélène (Comptes Rendus Biologies)
Fertility is declining worldwide and many couples are turning towards assisted reproductive technologies (ART) to conceive babies. Organisms that propagate via sexual reproduction often come from the fusion between two gametes, an oocyte and a sperm, whose qualities seem to be decreasing in the human species. Interestingly, while the sperm mostly transmits its haploid genome, the oocyte transmits not only its haploid set of chromosomes but also its huge cytoplasm to its progeny. This is what can be defined as the maternal inheritance composed of chromosomes, organelles, lipids, metabolites, proteins and RNAs. To decipher the decline in oocyte quality, it is essential to explore the nature of the maternal inheritance, and therefore study the last stages of murine oogenesis, namely the end of oocyte growth followed by the two meiotic divisions. These divisions are extremely asymmetric in terms of the size of the daughter cells, allowing to preserve the maternal inheritance accumulated during oocyte growth within these huge cells to support early embryo development. Studies performed in Marie-Hélène Verlhac’s lab have allowed to discover the unprecedented impact of original acto-myosin based mechanisms in the constitution as well as the preservation of this maternal inheritance and the consequences when these processes go awry.